Tuberous Sclerosis in Pregnancy - Sanjay N. Agrawal; Yoganand A. Kulkarni; Yogeshree R. Deshmukh; Subodh D. Jane (Our Dermatology Online, 2014)
Tuberous sclerosis is an autosomal dominant neurocutaenous disorder or neuroectodermatosis affecting multiple organ systems with variable clinical manifestations. We are reporting a case of a 26 years old female with history of epilepsy with mental retardation presented with fever and convulsions following an episode of stillbirth on first time with normal fetal outcome on second time. She had facial angiofibromas, shagreen patch, ash-leaf macules, periungual and subungual fibromas. She also had bilateral renal angiomyolipomas with haemorrhages and sub ependymal cortical tubers in brain. We report such a unique case having all clinically diagnostic physical sings of tuberous sclerosis with complicated obstetric history.